2001
DOI: 10.1074/jbc.m003642200
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Dependence of Collagenase (Matrix Metalloproteinase-1) Up-regulation by Elastin Peptides in Cultured Fibroblasts

Abstract: We have established that treatment of cultured human skin fibroblasts with tropoelastin or with heterogenic peptides, obtained after organo-alkaline or leukocyte elastase hydrolysis of insoluble elastin, induces a high expression of pro-collagenase-1 (pro-matrix metalloproteinase-1 (pro-MMP-1)). The identical effect was achieved after stimulation with a VGVAPG synthetic peptide, reflecting the elastin-derived domain known to bind to the 67-kDa elastin-binding protein. This clearly indicated involvement of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
148
1
3

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
4

Relationship

4
4

Authors

Journals

citations
Cited by 155 publications
(160 citation statements)
references
References 38 publications
8
148
1
3
Order By: Relevance
“…In previous work, we have established that hexapeptides interacting with EBP share the XGXXPG consensus sequence that is thought to stabilize a type VIII ␤-turn (30,31). Importantly, the conformation adopted by VGVAPG in our docking model is close to a type VIII ␤-turn.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…In previous work, we have established that hexapeptides interacting with EBP share the XGXXPG consensus sequence that is thought to stabilize a type VIII ␤-turn (30,31). Importantly, the conformation adopted by VGVAPG in our docking model is close to a type VIII ␤-turn.…”
Section: Discussionmentioning
confidence: 67%
“…EBP is known to interact with various agonists (13,(31)(32)(33)(34)(35). In previous work, we have established that hexapeptides interacting with EBP share the XGXXPG consensus sequence that is thought to stabilize a type VIII ␤-turn (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…This was achieved using 1 M KOH in 80% aqueous ethanol (36). The obtained mixture of elastin peptides is termed -elastin (kE) and exhibits the same biological and physical properties as elastin hydrolysates (5).…”
Section: Methodsmentioning
confidence: 99%
“…However, when Senior et al (4) demonstrated that elastin digestion products were chemotactic for neutrophils and macrophages, it became suddenly apparent that peptides derived from amorphous elastin could modulate cell physiology. In fact, it has been shown because that fibroblasts (5)(6)(7)(8)(9)(10)(11)(12), smooth muscle cells (7,(13)(14)(15), endothelial cells (16 -19), leukocytes (20,21), and lymphocytes (22) were sensitive to the presence of these peptides yielding a broad range of biological activities (see Ref. 23 for a review).…”
mentioning
confidence: 99%
“…Brassart and colleagues (32) reported that pertussis toxinsensitive G proteins and tyrosine kinase are involved in the EBP-mediated up-regulation of matrix metalloproteinase-2 in HT-1080 cancer cells. Because the abovementioned data clearly suggest that the cell surface EBP functions as a subunit of a true receptor capable of transmitting physiological signals from the extracellular matrix into the cell interior, the present studies have been aimed at a detailed disclosure of the intracellular signaling pathways generated by the association between elastin-derived peptides and the EBP.…”
mentioning
confidence: 99%